A comparison of barefoot and sprint spike conditions in sprinting - Toon, D.; Williams, B.; Hopkinson, N.; Caine, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2009)
The primary kinematic factors relating to sprinting performance may be influenced by the mechanical properties of the footwear worn. It was hypothesized that, compared with the barefoot condition, sprint spikes would influence sole angle to the ground, and metatarsophalangeal joint (MPJ) extension and flexion. High-speed video recording was used to analyse key kinematic variables of the foot segments and the MPJ in barefoot and shod running conditions. The stance phases of four sprinters (two male) were captured in the blocks, at 10 m and at 50 m into a maximal effort sprint. Angular range and angular velocity during MPJ flexion at 10 m and 50 m were reduced significantly when wearing sprint spikes. The mean angular range at 10 m was reduced by 11°, 13°, and 5° for the initial flexion phase, the extension phase, and the final phase of flexion respectively. This effect was larger during ground contact at 10 m versus 50 m. Sole angle to the ground at take-off was lower in the sprint spike shod condition than in the barefoot condition. Performance-related parameters such as degree of MPJ extension, MPJ extension velocity, and sole angle to the ground are influenced by sprint spikes when compared with the barefoot condition.